Removal of both Ycf48 and Psb27 in Synechocystis sp. PCC 6803 disrupts Photosystem II assembly and alters QA− oxidation in the mature complex. Issue 20 (27th August 2014) - Jackson, Simon A.; Hervey, John R.D.; Dale, Asher J.; Eaton-Rye, Julian J.
Abstract : The Photosystem II (PS II) assembly factors Psb27 and Ycf48 are transiently associated with PS II during its biogenesis and repair pathways. We investigated the function of these proteins by constructing knockout mutants in Synechocystis sp. PCC 6803. In ΔYcf48 cells, PS II electron transfer and stable oxygen evolution were perturbed. Additionally, Psb27 was required for photoautotrophic growth of cells lacking Ycf48 and assembly beyond the RC47 assembly complex in ΔYcf48:ΔPsb27 cells was impeded. Our results suggest the RC47 complex formed in ΔYcf48 cells is defective and that this deficiency is exacerbated if CP43 binds in the absence of Psb27. Abstract : Photosystem II assembly has been studied in a ΔYcf48:ΔPsb27 double deletion mutant. Photoautotrophic growth and oxygen evolution were impaired in ΔYcf48:ΔPsb27 cells. Electron transfer in the presence and absence of DCMU was modified in the single and double mutants. Photosystem II sub‐complexes accumulated in the ΔYcf48:ΔPsb27 strain. An assembly "bottleneck" at the level of the RC47 sub‐complex was observed.